Variations in pain induced by venous cannulation on repeated time-points : An observational cohort study - Johansson, Martin; Mogianos, Krister ; 0009-0009-0622-990X; Persson, Anna KM ; 0000-0002-9000-849X (Journal of Vascular Access, 2025)
BACKGROUND: Catheterization of the vein is frequently a painful procedure. Assessing venous cannulation induced pain (VCP) before surgery have been used to predict the intensity of postoperative pain and postoperative opioid consumption. The aim of this study was to investigate the intra-individual variation in venous cannulation induced pain at three consecutive time points and factors influencing levels of reported pain. METHODS: Participants (n = 101) were included at the blood-donor-center of a regional hospital in Sweden. All completed the Hospital Anxiety and Depression Scale and Pain Catastrophizing Scale and reported previous pain condition or ongoing use of analgesics upon inclusion. During three consecutive visits, venous cannulation was performed in a standardized manner, during which pain intensity was reported using the Visual Analogue Scale (VAS). RESULTS: The intra-individual variation in VCP, measured using the mean coefficient of variation, was 1.2. This means that the mean intra-individual difference in pain upon VCP between the three time points was 20%. A tendency toward higher intra-individual variation with higher pain intensities was found. Mean intra-individual range in VCP was 1.9 (SD 1.8) VAS-units. No correlation was found between anxiety- or depression nor pain catastrophizing and pain associated with venous cannulation. Subjects with preexisting pain conditions did not experience more pain in this situation. CONCLUSIONS: Venous cannulation pain intensities show low intra-individual variations. Subjects with higher pain intensity during venous cannulation are prone to greater intra-individual variations. If low pain perceived this is likely to repeat. To our knowledge this has never been investigated before and has implications for using pain evaluations as proxy for sensitivity measurements but also for how we handle patients with previous pain on venous cannulation.